2007
DOI: 10.1016/j.bone.2007.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Standard multivitamin supplementation does not improve vitamin D insufficiency after burns

Abstract: Children suffering severe burns develop progressive vitamin D deficiency because of inability of burned skin to produce normal quantities of vitamin D 3 and lack of vitamin D supplementation on discharge. Our study was designed to determine whether a daily supplement of a standard multivitamin tablet containing vitamin D 2 400 IU (10 μg) for 6 months would raise serum levels of 25-hydroxyvitamin D [25(OH)D] to normal. We recruited eight burned children, ages 5-18, whose families were deemed reliable by the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…By six months post-burn, serum albumin and total protein are normal [21] although the length of time it takes serum vitamin D Binding Protein to return to normal has not been studied.…”
Section: The Natural History Of Vitamin D Me-tabolism Post-burnmentioning
confidence: 95%
“…By six months post-burn, serum albumin and total protein are normal [21] although the length of time it takes serum vitamin D Binding Protein to return to normal has not been studied.…”
Section: The Natural History Of Vitamin D Me-tabolism Post-burnmentioning
confidence: 95%
“…In 32 children with a mean age of 4 years and 15% TBSA burns, those randomized to vitamin C, E, and zinc supplementation demonstrated significant reductions in lipid peroxidation and time required for wound healing [50]. Vitamin D insufficiency is also prevalent in children with severe burns and is not improved with multivitamin supplementation [51,52]. Vitamin D status may influence the course of illness in critically ill children.…”
Section: Monitoring Nutrition Therapymentioning
confidence: 97%
“…This is not rational particularly if the adverse health effect in question is: (i) mild and transient; (ii) is restricted to a specific population group whose exposure could be risk managed via labelling; (iii) where there is an overlap between risk and benefit; (iv) where other adverse health effects are known not to occur even with considerably higher intake levels, and (v) where significant benefits are to be achieved at higher intakes. Klein et al (2009) found that a multivitamin containing vitamin D (5 g [200 IU] D2) did not significantly raise circulating vitamin D levels in children burns victims, implying considerably higher doses would be required. Three forms of vitamin B3, namely nicotinic acid, niacinamide and inositol hexanicotinate, illustrate the importance of different intake-response relationships of various molecular forms; variation typically occurs between individuals (adaptation and physiological requirement) as well as within the same individual, temporally.…”
Section: Summary Of Modelmentioning
confidence: 98%